Culture of aesthetic emotion - O'Daniel, Anna Louella (My University, 1903)
Introduction: "Aesthetic emotion has its origin in the perception of the beautiful." The beautiful really exists in nature, in art, in spiritual character and life. Even the pleasurable feeling with which we greet the apprehension of the beautiful is itself beautiful. An object can not be beautiful if it can give pleasure to no one. It is an ultimate good and must satisfy a natural function to some fundamental capacity of our minds. But when asked what beauty really is we might reply as St. Augustin said of Time. "If unasked I know but when asked I know not.” The plastic arts, with poetry and music, are the most conspicuous monuments of this human history. They have attracted to their service an amount of effort, genius and honor which is little inferior to that which is given to industry, war or religion. It is not only in fine arts that man shows this susceptibility to beauty but in all the products of human industry he is attracted by appearance, and great sacrifice of tine and labor is given to beautify even its most vulgar manufactures. Our clothing, our dwellings and our companions are not selected without reference to their aesthetic qualities. The forms of many animals are due to the survival by sexual selection of the colors and forms most attractive to the eye.
The cultivation of the aesthetic emotions
Citation: O'Daniel, Anna Louella. Culture of aesthetic emotion. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Synthetic Philosophy; New Psychology; Psychology of Emotions; Theses